Dung Beetle Body Condition: A Tool for Disturbance Evaluation in Contaminated Pastures. (24th September 2019) - Villada‐Bedoya, Sebastián; Córdoba‐Aguilar, Alex; Escobar, Federico; Martínez‐Morales, Imelda; González‐Tokman, Daniel
Abstract: The use of veterinary medical products and herbicides is a common practice in intensified livestock systems. These compounds affect nontarget organisms that perform important ecosystem functions, such as dung beetles. The assessment of body condition allows us to determine how individuals respond to changes in the environment. However, assessments of how contamination associated with cattle farming affects coprophagous insects such as dung beetles have not been conducted in natural systems. In the present study, we evaluated the effect of ivermectin (an antiparasitic drug) and herbicides on the body condition of 3 species of dung beetles collected in the field: Copris incertus, Euoniticellus intermedius, and Digitonthophagus gazella . We recorded 3 condition indicators (body size, lipid mass, and muscle mass) of beetles collected from 19 livestock ranches in northeastern Mexico. In general, the use of ivermectin had adverse effects on C . incertus and E . intermedius whereas the effects were positive for D . gazella . Conversely, the use of herbicides had adverse effects on D . gazella and positive effects on C . incertus . The different effects of ivermectin and herbicides found in males and females show that sex can be important in determining individual responses to environmental contamination. Importantly, we provide the first evidence under natural conditions that native and exotic species of dung beetles are highly sensitive to different types of livestock management, with veterinary medications and herbicides having the ability to alter body condition. Changes in dung beetle condition can reduce the ecosystem services that dung beetles provide in livestock systems. Environ Toxicol Chem 2019;38:2392–2404. © 2019 SETAC